Effectiveness Of Cucumber Extract (Cucumis Sativus) In Reducing Cholesterol Levels In Mice (Mus Musculus) Induced By Hypercholesterolemia - Haikal Zanki; Bagas Ardiyantoro; Tatiana Siska Wardani (CV. AFDIFAL MAJU BERKAH, 2025)
Hypercholesterolemia is a global health problem and a major cause of cardiovascular disease. This study aims to explore the potential, determine the optimal dose, and identify the active compounds of cucumber (Cucumis sativus) ethanol extract as a cholesterol-lowering agent. Using a quantitative approach with a pure experimental method, a pre-test and post-test control group research design was applied in vivo to 25 mice (Mus musculus) divided into five treatment groups. The main instruments used included the Easy Touch cholesterol checker, and the data were analyzed using the One-Way ANOVA test. The results showed that cucumber extract had a significant effect in lowering cholesterol levels, with the effect increasing with dose. A dose of 700 mg/kgBW resulted in an average reduction of 49.51%, which was close to the effectiveness of simvastatin (54.05%). In conclusion, cucumber ethanol extract is a potential natural cholesterol-lowering agent, with a dose of 700 mg/kgBW being the most optimal dose that provides an effect almost comparable to that of standard drugs.